Seniority Principle in the European Labour Market with Emphasis on Slovakia - Dováľová, Gabriela; Hvozdíková, Veronika (European Scientific Journal, ESJ, 2017)
Income is without doubt an important indicator reflecting status of a person in the labour market. By comparing the wage dynamics decomposed by age groups, we try to reveal whether there is the seniority principle promoting accumulated working experience and skills in older age, or whether older people in the European countries face age discrimination in terms of earnings. Looking closely at the case of Slovakia, we point out the misinterpretation based on stereotypes about poor employment situation of older persons. In fact, median-age to pre-retirement age cohorts show less inactive and less unemployed persons compared to young generation. However, this is true only when considering employment rates. As regards income development, in average, older people can rarely expect their wage to rise with age. This is not just the case of Slovakia; the seniority principle in terms of earnings vanishing across the EU countries, particularly in old member states.